Preferência e competição alimentar em um grupo de Sapajus flavius em fragmento de Mata Atlântica em Caaporã – Paraíba – Brasil - Lins, Poliana Gabriele Alves de Souza (2015)
Feeding is the primary selective pressure in all forms of animals. Nutritional ecological models predict consequences of preferred and non-preferred food consumption on behavioural, physiological and morphological adaptations. At same time, socioecological models infer socio-organizarion patterns based on feeding competition faced by animals. A list of preferred foods, and inferences regarding the intensity of feeding competition and its behavioural consequences are information of much importance for management of populations in fragments. In this work we observed the feeding behavior and spatial positioning of a group of more than 100 blond capuchin monkeys (Sapajus flavius) that inhabit a fragment of Atlantic forest, surrounded by sugarcane plantation. We compared the consumption of different food items with their monthly availability in the area to define the preferred and fallback food items. We recorded the vocalizations of aggression and the inter-individual distance (area of Minimum Convex Polygon/n individuals) to infer the type of food competition experienced by animals. In the year studied the fruit feeding time correlated with top consumed fruit productivity, indicating preference for fruits. Our data indicate that the species Elaeis sp., Cecropia palmata, Inga spp. and Simarouba amara are the preferred food items in the diet. Available all year round and uniformly distributed, sugarcane was a regular item in the diet and its was characterized as a staple fallback food for this group. Although fruits are preferential food items, direct competition rate did not correlate to fruit productivity in the area, maintaining the high rates throughout the year (2.45 events/ hour). The inter-individual distance index positively correlated with rain fall indicating scramble food competition. The number of neighbours of females carrying infants was smaller when fruit productivity is low, indicating that females carrying infants are suffering increased indirect competition. Our data indicates that blond capuchins in this fragment make use of sugar cane as a staple fallback food, which evidence the importance of sugar cane landscape for the survival of this critically endangered capuchin species in fragmented habitats in Northeast Brazil. A preliminary list of preferred and important foods is offered, and can assist in the choice of trees for reforestation, better fragments to be preserved and areas of release and translocation of animals. We did not observe an increase of contest competition while using preferred foods, but when using staple FBF. This may be due the altered environment, which results in high competition food throughout the year. Both the food preference as the social and behavioral consequences of high food competition experienced by animals in this fragment must be accompanied over the years to ensure the survival of this population.